How Can Climate Models Be Used in Paleoelevation Reconstructions? - Botsyun, Svetlana; Ehlers, Todd A. (Frontiers in Earth Science, 2021)
Paleoelevation reconstructions derived from proxy data such as stable oxygen isotope records in terrestrial archives have been determined for Cenozoic mountain ranges around the world. Recent studies have highlighted that a variety of paleoclimate processes can contribute to the isotopic composition of a measured precipitation (δ18Op) signal used in elevation reconstructions. These processes can include: regional, global, and topographic variations in paleotemperature; environmental conditions of an air mass before orographic ascent; evapotranspiration; water vapor recycling; and changes in the vapor source. In some cases, these processes can overprint the elevation signal sought in proxy data and preclude robust elevation reconstructions. Recent advances in isotope tracking climate models allow us to estimate paleoclimate changes during orogen development and associated changes in paleo δ18Op due to both climate and topographic changes. These models account for adiabatic and non-adiabatic temperature changes, relative humidity variations, changing continental evapotranspiration, vapor recycling, vapor source changes, etc. Modeling strategies using high-resolution isotopes-enabled General Circulation Models (iGCMs) together with time-specific boundary conditions and variable topography provide a powerful tool for enhancing elevation reconstructions from δ18Op proxy data. In this review, we discuss the principles, benefits and caveats of using iGCMs for interpreting isotopic records from natural archives for paleoelevation reconstructions. We also highlight future challenges for the application of iGCMs to paleoaltimetry proxy data that open up new avenues for research on tectonic-climate interactions.